Frontières morales et catégories culturelles : Penser la spiritualité au prisme de la conversion au christianisme des Népalo-bhoutanais - Boucher, Guillaume (Anthropologica, 2023)
If the Christianized Nepali-Bhutanese among whom I conducted my doctoral studies in the region of Saint-Jérôme, Quebec, do not have recourse to the term “spirituality,” it is nevertheless possible to observe that “people are engaged in moral boundary work (…) setting out distinctions that allow status comparisons based on qualities judged as virtuous” (Ammerman 2013, 275) in the narrative surrounding their conversion. This work can be observed at the forefront of interactions in the refugee camps where they stayed in Nepal and in Quebec. The conversion to Christianity is accompanied by a series of discourses by Hindus, Christians, and the agents who helped resettle the refugees in Quebec. Although these discourses generally seem to follow the contours of categories defined by Ammerman in her study of spirituality, a nuanced approach must be taken with respect to ethical discourses that develop around conversion and belonging to a group of converts.